Analisis Indeks Kekeringan Daerah Aliran Sungai Batang Anai Dengan Menggunakan Metode Standardized Precipitation Index - Nurhasanah Nurhasanah; Manyuk Fauzi; Trimaijon Trimaijon (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
There are several problems related to water resources such as floods and drought. One of the critical issue is drought. Drought is a nature phenomenon which is considered as common dangers which occurs in accordance of climate cycle related to hydrological cycle that affected by rainfall. Drought that affected only by rainfall is meteorological drought which is an early indication of drought. Based on the large impact, it is necessary to analyze index of dryness to find out the level of dryness as the early warning of further droughts. The location of the research was the Batang Anai watersheds which is one of water source of agricultural sector in Sumatera Barat Province. Standardized Precipitation Index (SPI) was one of the methods to analyze drought index in an area. The calculation was done based on rainfall data of half monthly period and monthly period from 1997 to 2016 on every rain station in DAS Batang Anai. The result of SPI drought index was correlated with Indian Ocean Dipole (IOD) phenomenon and then was mapped using ARC GIS software with tools Polygoon Thiessen. The final result of this research showed that in half period the highest value of drought index was -2,3811 (January, 1st periode, 2013) with extreme drought classification. While in monthly period, the value of drought index was -1,9183 (January, 2012) with very dry classification. This research also showed the suitability of SPI drought index with IOD drought phenomenon which has suitable average 70,14%.Keywords : Drought index, Standardized Precipitation Index, GIS, Indian Ocean Dipole